Distribution of FMR1 alleles in the Vietnamese pregnant population: Implications for a national screening strategy - Truong, Nguyen Van; Lan, Hoang Thu; Ngoc, Nguyen Thi Minh; Trang, Dao Thi; Anh, Nguyen Huu Duc; Mai, Nguyen Phuong; Nguyet, Doan Thi; Van, Nguyen Thi Khanh; Tu, Ho Cam; Ai, Nguyen Thi Thuy; Hai, Tang Xuan; Hao, Nguyen Thi; et al. (Tạp chí Nghiên cứu Y học, 2026)
The expansion of cytosine-guanine-guanine (CGG) trinucleotide repeats in the 5′-untranslated region (5’-UTR) of the FMR1 gene leads to a spectrum of multisystem conditions collectively referred to as FMR1-related disorders. This study aimed to evaluate the prevalence of FMR1 allele groups among 4,000 pregnant women, thereby elucidating the genetic landscape of FMR1 within the Vietnamese population. A multicenter cross-sectional study was conducted. Peripheral blood samples were obtained for genotyping, and data collection for analysis involving demographic, clinical, and family history. The observed frequencies of the normal, intermediate, and premutation allele carriers were 98.85%, 1.1%, and 0.05%, respectively, while no full mutation carriers were detected. A statistically significant association was observed between the distribution of FMR1 allele groups and risk stratification based on family history. The Vietnamese population may exhibit a lower risk for FMR1-related disorders. Consequently, a targeted screening strategy focusing on high-risk individuals, rather than universal screening, may be a more pragmatic and cost-effective approach within the Vietnamese healthcare context.